Enterprise risk management manufacturing industry quality determinants - Ratna Marta Dhewi; Hendrian Martunus; Nurul Hidayah; Erna Setiany (Brazilian Journal of Operations & Production Management)
Goal: Large manufacturing companies face significant risks due to importing raw materials and exposure to fluctuating exchange rates. Enterprise Risk Management (ERM) is vital in this sector to manage its distinctive risks. This study finds ERM factors in Indonesia and Malaysia that affect company value and empirically evaluates risk management in their organizations.